Secondary Budd–Chiari syndrome caused by renal cell carcinoma with hepatic vein invasion: case report - Adil Ibrahim; Tasabeeh Ahmed; Rayan Khalid; Imad Fadl-Elmula (African Journal of Urology)
Abstract Background Budd–Chiari syndrome (BCS) is a rare condition characterized by the blockage of the hepatic venous outflow tract. Primary Budd–Chiari syndrome occurs when the blockage is primarily due to a venous process such as thrombosis or phlebitis. In contrast, secondary BCS is caused by the compression or invasion of the hepatic veins and/or the inferior vena cava by a lesion originating outside the vein, such as a malignancy. Case presentation We present a unique case involving a large renal cell tumor that extended into the inferior vena cava and necessitated a referral for radical nephrectomy from a regional hospital. Unexpectedly, 2 days prior to the surgery, the patient deteriorated and developed secondary Budd–Chiari syndrome, which was confirmed by an abdominal CT scan revealing the tumor's extension into the hepatic veins. Before the best treatment option decided, a hepatologist was call for consultations and according to him surgical intervention with a post-operative anticoagulant therapy is the best option due to the extension of a tumor thrombus. Right radical nephrectomy involves the exploration and evacuation of a tumor thrombus from the renal vein, inferior vena cava, and hepatic vein was done. Following an uneventful postoperative period, the patient was discharged in good condition and referred to the oncology department for further management. Conclusions This situation highlights the need to consider the possibility of secondary Budd–Chiari syndrome in patients with large renal cell carcinoma. Being aware of this potential complication may help improve patient outcomes, especially in areas with limited healthcare resources, where late diagnoses of large renal cell carcinoma are frequent.